2019
DOI: 10.1039/c8cp07580h
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and reactivity of Fe(iv)oxo species in metal–organic frameworks

Abstract: We investigate the potential use of Fe(iv)oxo species supported on a metal–organic framework in the catalytic hydroxylation of methane to produce methanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…Pure density functionals are typically preferred in solid state applications, because of their reduced computational cost, especially in plane-wave based calculations and ab initio molecular dynamics simulations. [38][39][40][41][42][43][44] In previous work 14 we showed that B3LYP, which provides a reasonably accurate description of high-spin Fe(IV)oxo states, 45,46 is also more adequate than most generalised-gradient approximations (e.g. PBE and BLYP) in the solid state.…”
Section: Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pure density functionals are typically preferred in solid state applications, because of their reduced computational cost, especially in plane-wave based calculations and ab initio molecular dynamics simulations. [38][39][40][41][42][43][44] In previous work 14 we showed that B3LYP, which provides a reasonably accurate description of high-spin Fe(IV)oxo states, 45,46 is also more adequate than most generalised-gradient approximations (e.g. PBE and BLYP) in the solid state.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…In recent work based on solid-state calculations carried out at the B3LYP level of density-functional theory (DFT), we have shown that the MOFs can provide a close to ideal coordination environment for the stabilisation of highly reactive Fe(IV)O groups. 14 MOFs 15 are an intriguing and widely studied class of solid-state materials with a variety of applications, including heterogeneous catalysis, gas separation, carbon capture, and hydrogen storage. Extensive work, both experimental and theoretical has been devoted to characterise the structural and chemical properties of these materials and to optimise their ability to act as catalysts for a variety of synthetic processes.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with recent computational work on the hydroxylation of methane using Fe(IV)oxo in MOF-74. 25 However, in this case, the adsorption enthalpy from A (the bare cluster) to B (the N 2 O bound to Fe of A) is less than that of the quintet pathway (2.2 kcal mol À1 vs. 8.5 kcal mol À1 ), and the relative energy of the reactant is generally higher than that of the quintet surface at least 37.5 kcal mol À1 . Note that the activation barrier 5 TS2 and 5 TS3 on quintet surface are just 3.5 and 4.7 kcal mol À1 which are also less than those of 5.2 and 7.9 kcal mol À1 on triplet, respectively.…”
Section: Catalytic Cycle For the Oxidation Of 14-cyclohexadiene (Chd)mentioning
confidence: 86%
“…Noticing this enormous knowledge gap and that the family of MOF-74 has been identified as a potential candidate to catalyse the methane activation, 32 we have recently used densityfunctional theory (DFT) calculations to assess the ability of MOFs to act as suitable guests for Fe(IV)O catalytic centres and their reaction substrates. 21,33 We have shown that MOF-74 can indeed be used to stabilise quintet Fe(IV)O groups, which can act as catalytic centres for substrate molecules adsorbed in the MOF cavities. In MOF-74, the coordination geometry of Fe(IV)O is close to the ideal one postulated from gas-phase calculations, 23 with four oxygen atoms in the equatorial positions, a relatively unhin-dered axial coordination site and the Fe-O axis point toward the interior of the cavity and easily accessible to the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…14,15,[17][18][19] It has been also shown that one of the most complex characteristic of Fe(IV)O is the frequent presence of several competing spin states, and the consequent appearance of two-and multi-state reactivity. 20 Typically, quintet and triplet states can be close in energy, 21 but they exhibit different chemical properties and reaction pathways. In most situations, quintet systems show higher electrophilicity and oxidative activity, and they can therefore act as powerful electron acceptors.…”
Section: Introductionmentioning
confidence: 99%